Temperature of and heat flux density from the external ocular surface in diabetic retinopathy patients: a pilot study (Ukrainian Journal of Ophthalmology, 2025)
Background: Heat exchange characteristics include not only temperatures and temperature distribution, but also heat flux (HF).Purpose: To examine temperature of and density of HF from the ocular surface in the eyes of patients with diabetic retinopathy (DR).Material and Methods: Sixty-two patients (123 eyes) with DR were under observation. Of these, 28 (55 eyes) and 34 (68 eyes) were diagnosed with non-proliferative DR (NPDR) and proliferative DR (PDR), respectively. They underwent a general clinical examination and measurements of temperature of the external corneal surface and density of HF from the eye. In addition, all NPDR patients underwent rheoophthalmography (ROG).Results: There was a significant difference in density of HF from the ocular surface (7.3 ± 2.1 mW/cm2 vs 6.3 ± 1.6 mW/cm2; p = 0.002), but not in ocular surface temperature (34.7 ± 1.3 °С vs 34.8 ± 1.1 °С; p = 0.8) between NPDR patients and PDR patients. HF density from the eye was positively correlated with the ocular blood volume coefficient (RQ; also named the rheographic coefficient) as assessed by ROG (r = 0.5; p = 0.01) for patients with NPDR. There was a relationship between the density of heat flux from the ocular surface and age of DR patients.Conclusion: Preliminary results suggest that (1) compared to the temperature of the ocular surface, the heat flux from the ocular surface better reflects the status of heat exchange in the eye, and (2) the technique might be promising as a diagnostic test for various pathological conditions involving impaired heat processes in the eye.
Keywords: thermoelectric device; temperature of the external ocular surface; heat flux density; rheoophthalmography; diabetic retinopathy